How do IoT products influence people’s lifestyle and improve E-commerce? - Yeung, Minggaak (2019)
The evaluation of the Internet of Things (IoT) has been widespread in different industries which played an essential role in this technology era. It is one of the most critical areas of future technology and is currently receiving attention from all walks of life. IoT offers the bridge to build the network of physical devices and appliance that could interact with each other. In this paper, there are concepts, theory, business cases will be applied to examines how do IoT products influence people’s lifestyle and improve E-business in different aspects. In response to answer research questions, this paper introduces the leading technologies of IoT. Also, the Kano model and Lifestyle balance model are applied to analyse the infuriation of how IoT affect people’s lifestyle which aims to prove there are differences of using IoT and without IoT in people’s life. Moreover, further analysis of the relationship between IoT and e-commerce in the business ecosystem model and how do IoT improves E-commerce. Given the above analysis, this paper further discusses and gives suggestions in relation to the issues covered throughout this paper.